Invertebrados marinos eocenos de los cerros Palique y Castillo, sudoeste de la provincia de Santa Cruz, Argentina (Ameghiniana, 2014)
"A small fauna of mollusks is described and illustrated for the first time from cerro Palique and cerro Castillo. The material from cerro Palique comes from beds that can be correlatedto the upper part of the Río Turbio Forrnation, due to the presence of Venericardia (Venericor) sp. The material from cerro Castillo was collected from the Eocene Man Aike Formation. Bouchardia zitteli Ihering, recorded from both localities, is a species with wide austral distribution (San Julián Forrnation, El Chacay Forrnation) and it is also frequent in the Antarctic Eocene. The bivalve V. (Venericor) has a Pacific origin and shows similar biostratigraphic distribution in western and eastern Patagonian regions."